Risk factors associated with loneliness among mexican-origin adults in southern Arizona - Mario Morales; Ada M. Wilkinson-Lee; Maia Ingram; Thomas Nuño; Jill E. Guernsey De Zapien; Ramses Sepulveda; Scott Carvajal (BMC, 2024)
Abstract This study examines factors associated with symptoms of loneliness among a sample (n = 213) of mostly Mexican-origin adults at risk of chronic diseases in Southern Arizona's Pima, Yuma, and Santa Cruz counties. It uses baseline data from a community-based participatory research partnership and multinominal logistic regression models. Controlling for chronic diseases and sociodemographic characteristics, perceived social support and hope exhibit negative main effects on loneliness when comparing individuals who experienced loneliness for 5-7 days in the preceding week with those who did not encounter such feelings during the same period (adjusted odds ratio, AOR = 0.49 and 0.47; 95% confidence interval, CI = 0.34-0.73 and 0.29-0.75, respectively). However, when considered together, perceived social support and hope display a positive and statistically significant combined effect on loneliness (AOR = 1.03; 95% CI = 1.01-1.06). Holding all covariates constant, individuals reporting loneliness for 5-7 days exhibit a relative risk ratio of 1.24 (95% CI = 1.06-1.46) for a one-unit increase in physical problem severity compared to those who do not experience loneliness. Moreover, being 65 years old or older (AOR = 0.16, 95% CI = 0.03-0.84), and having been born in Mexico and lived in the US for less than 30 years (AOR = 0.12, 95% CI = 0.02-0.74) are associated with negative main effects on loneliness when comparing individuals who experienced loneliness 1-2, and 5-7 days in the preceding week with those who did not feel loneliness during the same timeframe, respectively. Recognizing the crucial role of loneliness in shaping health outcomes for Mexican-origin adults, our findings underscore the significance of fostering supportive environments that not only enhance well-being but also cultivate robust community bonds within the US-Mexico border region.